Health literacy profiling of parents in two disadvantaged inner-city areas in the United Kingdom - Samantha Belfrage; Margaret Husted; Simon Fraser; Sanjay Patel; James Faulkner (Health Literacy and Communication Open)
Background Health literacy refers to the skills needed to access, understand, and navigate health information and services. Limited parental health literacy is associated with ineffective preventive behaviours and worse child health outcomes. People with limited financial and social resources are more likely to have limited health literacy. Profiling health literacy strengths and limitations of a population allows the multidimensional nature of health literacy to be considered and highlight patterns of need.Aims This study aimed to identify the health literacy profiles of parents of children aged 0–4 years in two cities in the United Kingdom with high levels of deprivation (Portsmouth, Southampton), and develop vignettes to illustrate their diverse experiences.Methods A mixed-methods approach was employed using the Optimising Health Literacy and Access framework. Quantitative data were collected using the Health Literacy Questionnaire-Parent version (HLQ-Parent) among parents from two cities. Hierarchical cluster analysis was performed on the HLQ-Parent data to identify clusters reflecting varied health literacy strengths and limitations across its nine domains. Demographic data enriched the profiles. Qualitative data from semi-structured interviews contextualized the clusters, with vignettes created to represent each profile in an explanatory sequential design.Results A total of 175 participants (mean age 33 years; 98% female) completed the HLQ-Parent. Eight clusters with distinct health literacy profiles emerged. In both cities, one cluster (44% of participants) exhibited high scores across all domains, while another cluster (20% of participants) displayed significant challenges across all domains. Eight vignettes were created to represent the lived experiences of parents within each health literacy profile, highlighting the unique strengths and challenges faced by each cluster.Discussion This study provides a deeper understanding of how parents use health information and navigate services to manage their children’s health and wellbeing. The findings highlight that a one-size-fits-all approach to improving health literacy would overlook those with the greatest needs, emphasising the importance of developing interventions to the unique characteristics of each identified health literacy cluster. The vignettes developed will inform future research, including stakeholder workshops, to co-design targeted health literacy interventions and solutions, ensuring they address the specific strengths and challenges identified in this study.